Fructose Induces Pulmonary Fibrotic Phenotype Through Promoting Epithelial-Mesenchymal Transition Mediated by ROS-Activated Latent TGF-β1 - Xu, Xiaoxiao; Ma, Chuang; Wu, Hang; Ma, Yuanqiao; Liu, Zejin; Zhong, Peijie; Jin, Chaolei; Ning, Wenjuan; Wu, Xiao; Zhang, Yijie; Han, Jichang; Wang, Junpeng (Frontiers in Nutrition, 2022)
Fructose is a commonly used food additive and has many adverse effects on human health, but it is unclear whether fructose impacts pulmonary fibrosis. TGF-β1, a potent fibrotic inducer, is produced as latent complexes by various cells, including alveolar epithelial cells, macrophages, and fibroblasts, and must be activated by many factors such as reactive oxygen species (ROS). This study explored the impact of fructose on pulmonary fibrotic phenotype and epithelial-mesenchymal transition (EMT) using lung epithelial cells (A549 or BEAS-2B) and the underlying mechanisms. Fructose promoted the cell viability of lung epithelial cells, while N-Acetyl-l-cysteine (NAC) inhibited such. Furthermore, fructose promoted the proliferation of lung epithelial cells. Co-treatment of fructose and latent TGF-β1 could induce the fibrosis phenotype and the epithelial-mesenchymal transition (EMT)-related protein expression, increasing lung epithelial cell migration and invasion. Mechanism analysis shows that fructose dose-dependently promoted the production of total and mitochondrial ROS in A549 cells, while NAC eliminated this promotion. Notably, post-administration with NAC or SB431542 (a potent TGF-β type I receptor inhibitor) inhibited fibrosis phenotype and EMT process of lung epithelial cells co-treated with fructose and latent TGF-β1. Finally, the fibrosis phenotype and EMT-related protein expression of lung epithelial cells were mediated by the ROS-activated latent TGF-β1/Smad3 signal. This study revealed that high fructose promoted the fibrotic phenotype of human lung epithelial cells by up-regulating oxidative stress, which enabled the latent form of TGF-β1 into activated TGF-β1, which provides help and reference for the diet adjustment of healthy people and patients with fibrosis.